2004
DOI: 10.2298/jsc0409641r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of Ni(II), Cu(II) and Co(III) complexes with polyamine-containing macrocycles bearing an aminoethyl pendant arm

Abstract: Reaction of [M(ppn)2]X2 (where M = Cu(II), Ni(II), Co(II) and ppn = 1,3-diaminopropane) with formaldehyde and ethylenediamine in methanol results in the ready formation of a 16-membered macrocyclic complex. The complexes were characterized by elemental analysis, IR, EPR, electronic spectral data magnetic moments and conductance measurements. The Cu(II), Ni(II) and Co(III) complexes are coordinated axially with both pendant groups of the hexadentate macrocycle. These pendant donors are attached to the macrocycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 11 publications
5
9
0
Order By: Relevance
“…The magnetic susceptibility measurement after diamagnetic corrections yielded a magnetic moment of 4.85 BM which is close to that expected for an octahedral Co(II) complexes [15,16]. The electronic absorption spectrum showed two absorption bands (as shown in table (3) at (13513 & 18691) cm -1 which is considered as υ 2 and υ 3 respectively.…”
Section: Co-complex (C 2 )supporting
confidence: 77%
See 2 more Smart Citations
“…The magnetic susceptibility measurement after diamagnetic corrections yielded a magnetic moment of 4.85 BM which is close to that expected for an octahedral Co(II) complexes [15,16]. The electronic absorption spectrum showed two absorption bands (as shown in table (3) at (13513 & 18691) cm -1 which is considered as υ 2 and υ 3 respectively.…”
Section: Co-complex (C 2 )supporting
confidence: 77%
“…At room temperature the magnetic susceptibility measurement after diamagnetic corrections yielded a magnetic moment of 3.92 BM which is close to that expected for an octahedral Cr(III) complexes [15,16]. The Uvvisible spectrum of the dark green solution of chromium the Cr(III) complex showed three bands with the absorbance maxima at 15267 cm -1 , 20202 cm -1 and 32595 cm -1 which were considered as υ 1 , υ 2 , and υ 3 absorption bands respectively (table 3).…”
Section: Cr-complex (C 1 )supporting
confidence: 77%
See 1 more Smart Citation
“…This complex displayed that the spectra is axially symmetrical with no hyperfine splitting. Commonly [24]. It concluded that the presented complex have high g|| value of four N donors sites, which consist of a six coordinated complex 3 has a distorted octahedral Cu(II) ion.…”
Section: Esi-mass Spectramentioning
confidence: 81%
“…The electronic spectral data of Cu(II), Co(II) and Ni(II), complexes of the ligand BTMTA were recorded in DCM and the spectral data are given in Table.3 . The brown colored Cu(II) complex exhibit a broad asymmetric band in the region 12275-16262 cm -1 with maxima at 15194 cm -1 in an distorted octahedral geometry [31,32]. The broadness of the band may be due to dynamic Jahn-Teller distortion and is assigned to 2 T 2g → 2 E g transitions.…”
Section: Electronic Spectral and Magnetic Moment Data Of The Metal Comentioning
confidence: 99%